PEMIKIRAN ULAMA HANAFIYAH TENTANG PEMANFAATAN BARANG GADAI - Mahmudi . (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2013)
Basically, this mortgage is done because of the urgent need for all so difficult when lending to others without giving credence goods as a collateral loan. According to scholars Hana>fiyah recipient lawful liens not take any benefit from pawning goods in any way, although there is consent of the owner, since such means as to permit usury, because the debt will be given full pay, then that means the excess benefit. So because of these advantages there are usury laws. And Ulama Hana>fiyah stated that lien is considered perfect if the goods are pawned it was legally pawn in the hands of the receiver, and the money needed has been received by the pledgor. Lien perfection by scholars Hana>fiyah referred to as al-qabd al-marhu>n the collateral held by law, if the guarantee had been controlled by creditors then rahn contract that binds both parties